Testicular Cancer—Surgical Treatment - Vaz, Rodrigo Markus; Bordenali, Gustavo; Bibancos, Mauro (Frontiers in Endocrinology, 2019)
Testicular Germ Cell Tumor (GCT) is the most common solid tumor in men between the ages of 20-44. Men diagnosed with GCT have excellent survival rates due to advances in the multimodal treatment paradigm of chemotherapy, radiation therapy and surgery. When considering the adequate treatment, several variables should be investigated and known to select the proper procedure. Therefore, when considering Testicular Intra-Epithelial Neoplasia, organ-sparring treatment, such as radiotherapy or organ-sparring surgery should be considered, reaching a cure rate of 98%. However, when the case is of a seminoma or a non-seminoma, orchiectomy is usually the chosen procedure, reaching an oncological cure rate of 80-85%, when there is no metastasis. Retroperitoneal Lymph Node Dissection (RPLND) is generally considered as a treatment option for non-seminomas, when lymph nodes are compromised. There are three different RPLND techniques: open, laparoscopic and robotic. The open approach is as effective as the other two in its oncological efficiency. Although, when considering both laparoscopic and robotic approach, hospital stays are significantly reduced, better cosmetic results and less complications when compared to the open approach. Both laparoscopic and robotic approaches require extensive experience and have a steep learning curve, while also providing similar outcome, however, recent studies have been pointing out a slight increase of advantages on the robotic approach. Therefore, further studies are necessary to assert the robotic approach superiority. Also, it is noteworthy that new technologies are on the rise, improving the laparoscopic approach, requiring further studies after their uses are consolidated.